CodeBoost : a framework for transforming C++ programs - Bagge, O.S.; Haveraaen, M.; Visser, Eelco (My University, 2001)
Often we are faced with the need to make trivial, albeit tedious, changes to program code. It may be things like making variable names more readable, add code that will provide execution profile information, or change the style of a program from from expression oriented to object oriented in order to improve run-time efficiency. Such source-tosource transformations can be aided by, or even completely automatised, with the aid of a suitable program transformation tool. Here we present the CodeBoost framework for the implementation of source-to-source transformation of C++ programs. It is implemented using OpenC++ for the syntax analysis and using Stratego for defining the program transformations. Stratego allows for the easy expression of context sensitive transformations, a central point when using transformations to improve execution speeds of code. We also discuss two example applications.
Keywords: Wiskunde en Informatica